Magnetically Recoverable TiO2/SiO2/γ-Fe2O3/rGO Composite with Significantly Enhanced UV-Visible Light Photocatalytic Activity - Reyhaneh Kaveh; Maryam Mokhtarifar; Mojtaba Bagherzadeh; Andrea Lucotti; Maria Vittoria Diamanti; MariaPia Pedeferri (Molecules, 2020)
In this paper, we report the preparation of a new composite (TiO2/SiO2/γ-Fe2O3/rGO) with a high photocatalytic efficiency. The properties of the composite were examined by different analyses, including X-ray diffraction (XRD), field emission scanning electron microscope (FE-SEM), photoluminescence (PL), UV-Visible light diffuse reflectance spectroscopy, Fourier transform infrared spectroscopy (FTIR), Raman, vibrating-sample magnetometer (VSM), and nitrogen gas physisorption (BET) studies. The photocatalytic efficiency of the proposed composite was evaluated by the degradation of methylene blue under UV and visible light, and the results were compared with titanium dioxide (TiO2), where degradation increased from 30% to 84% and 4% to 66% under UV and visible light, respectively. The significant increase in photocatalytic activity may be explained by the higher adsorption of dye on the surface of the composite and the higher separation and transfer of charge carriers, which in turn promote active sites and photocatalytic efficiency.